2016
DOI: 10.1111/mpp.12410
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Botrytis–plant interactions using PathTrack©—an automated system for dynamic analysis of disease development

Abstract: The measurement of disease development is integral in studies on plant-microbe interactions. To address the need for a dynamic and quantitative disease evaluation, we developed PathTrack , and used it to analyse the interaction of plants with Botrytis cinerea. PathTrack is composed of an infection chamber, a photography unit and software that produces video files and numerical values of disease progression. We identified a previously unrecognized infection stage and determined numerical parameters of pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…To gain insight into possible unnoticed effects caused by BcXYG1, particularly during the early infection stage, we characterized infection of the bcxyg1 overexpression and deletion strains using the PathTrack system. This system allows for sensitive and quantitative analysis of infection dynamics and, therefore, can reveal small changes in disease development (Eizner et al, 2017). The pathogenic behavior of the Dbcxyg1 deletion strain was similar to that of the wild type in all of the examined parameters, including time and magnitude of early necrosis, break time, and lesion expansion rate (Fig.…”
Section: Bcxyg1 Contributes To the Production Of Local Necrosis Durinmentioning
confidence: 80%
See 4 more Smart Citations
“…To gain insight into possible unnoticed effects caused by BcXYG1, particularly during the early infection stage, we characterized infection of the bcxyg1 overexpression and deletion strains using the PathTrack system. This system allows for sensitive and quantitative analysis of infection dynamics and, therefore, can reveal small changes in disease development (Eizner et al, 2017). The pathogenic behavior of the Dbcxyg1 deletion strain was similar to that of the wild type in all of the examined parameters, including time and magnitude of early necrosis, break time, and lesion expansion rate (Fig.…”
Section: Bcxyg1 Contributes To the Production Of Local Necrosis Durinmentioning
confidence: 80%
“…Accordingly, mutants in NIP-encoding genes are expected to be affected specifically in the production of early necrosis, but not at the stage of spreading lesion. To determine the possible effect of BcXYG1 in an early stage of the disease, we analyzed the infection of bean leaves using PathTrack, a noninvasive, automated system for live imaging and quantitative measurement of disease development (Eizner et al, 2017). This analysis revealed that the leaves infected with the BcXYG1 overexpression strains OEXYG1 or OEMXYG1 produced earlier and more intense local necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations